The use of a computer simulation to promote conceptual change: A quasi-experimental study - Trundle, Kathy Cabe; Bell, Randy L. (Computers and education, 2010)
This mixed-methods investigation compared the effectiveness of three instructional approaches in achieving desired conceptual change among early childhood preservice teachers ( n = 157). Each of the three treatments employed inquiry-based instruction on moon phases using data collected from: (1) the planetarium software program, Starry Night™, (2) nature observations and Starry Night™, or (3) nature observations alone. Data sources included drawings, intensive interviews, and a lunar shapes card sort. The data sets were analyzed via a constant comparative method in order to produce profiles of each participant’s pre- and post-instruction conceptual understandings of moon phases. Non-parametric tests of significance revealed that pre- to post-instruction gains were significant for all three treatments across all targeted concepts. The Starry Night™-Only treatment demonstrated statistically greater gains for sequencing moon phases than the other two treatments. However, there were no significant differences among the three treatments in regard to participants’ abilities to draw scientific moon shapes or in their conceptions of the causes of moon phases. Thus, the three treatments were equally effective in facilitating desired conceptual change.